Students as Stakeholders: Understanding Expectations Can Increase Student Retention. (May 2022) - James, Jennifer L.
Adult student persistence in online programs is lower than in traditional college classrooms, but more adult learners are enrolling in online programs. Little research is available on students' needs and expectations for their success in online courses. A quantitative correlational study was conducted on student expectations of online learning using persistence factors of time, technological skills, and difficulty. Nontraditional students experience unique challenges to academic development stemming from problems at home, low-socioeconomic status, minimal off-campus support, and isolating discourse of academia. The intent of this article is to present new data on connections between student expectations and their persistence. Data were collected from 205 participants, 24 years or older, enrolled in at least one course in a series of online courses. Two factors were identified as significant correlations with student persistence: (a) difficulty level of course content and (b) time commitment.